International collaborative follow-up investigation of graduating high school students' understandings of the nature of scientific inquiry: is progress Being made?. Issue 7 (3rd May 2021) - Lederman, J. S.; Lederman, N. G.; Bartels, S.; Jimenez, J.; Acosta, K.; Akubo, M.; Aly, S.; Andrade, M. A. B. S. de; Atanasova, M.; Blanquet, E.; Blonder, R.; Brown, P.; et al.
ABSTRACT: Understandings of the nature of scientific inquiry (NOSI), as opposed to engaging students in inquiry learning experiences, are included in science education reform documents around the world. However, little is known about what students have learned about NOSI during their pre-college school years. The purpose of this large-scale follow-up international project (i.e. 32 countries and regions, spanning six continents and including 3917 students for the high school sample) was to collect data on what exiting high school students have learned about NOSI. Additionally, the study investigated changes in 12th grade students' NOSI understandings compared to seventh grade (i.e. 20 countries and regions) students' understandings from a prior investigation [Lederman et al. (2019). An international collaborative investigation of beginning seventh grade students' understandings of scientific inquiry: Establishing a baseline. Journal of Research in Science Teaching, 56(4), 486–515. https://doi.org/10.1002/tea.21512 ]. This study documents and discusses graduating high school students' understandings and compares their understandings to seventh grade students' understandings of the same aspects of scientific inquiry for each country. It is important to note that collecting data from each of the 130+ countries globally was not feasible. Similarly, it was not possible to collect data from every region of each country. A concerted effort was made, however, to provide a relatively representative picture of each country and the world.